Process and technology solutions for improving the energy efficiency and the sustainability of the iron ores reduction with Blast Furnaces utilizing synthesis gas - S. Andreola; F. Barbetti; L.E. Basini; G. Iaquaniello; A. Salladini (Cleaner Engineering and Technology)
This work examined solutions for improving the environmental impact and the economics of the iron ore reduction processes using Blast Furnaces and Basic Oxygen Furnaces. The improvements followed from the utilization of a syngas produced with Short Contact Time-Catalytic Partial Oxidation. The case studies considered a hot metal production of 2.35 MTPY and the effects of injecting synthesis gas (55,000 Nm3/h) on the reduction of coke utilization, CO2 and pollutants emissions. In addition, an economic analysis estimated the monetary value of Carbon Dioxide and air pollutant emissions avoidance. Cases in which syngas was produced by utilizing i) Natural Gas, ii) biogas and iii) mixtures of Natural Gas with Blast Furnace Gas and Coke Oven Gas were examined. Process schemes including electrolytic technologies were also considered. In these last cases, the Oxygen was utilized in the syngas production while the Hydrogen was added afterwards to the produced syngas. The results showed that the utilization of syngas allowed a reduction of coke consumption comprised between 13.4 and 39.4 kg/ton Hot Metal depending on the reactor's feedstock and process conditions. The economics also included sensitivity analysis for identifying the most attractive scenarios for pursuing the application of the examined solutions.